An experimental investigation on effects of nanofiber interleaves on fracture toughness of FRP laminates - Tharayil Santhoshkumar, Abhirama (2018)
Fiber Reinforced Polymers are widely used in many major industries due to their high Specific strength and stiffness. Many methods are carried out on them, prior to use to increase their delamination resistance, especially for safety-critical applications. This project investigated the impact of a commercially available thermoplastic nano-fiber interleaving material called Xantu.Layr on delamination resistance of various FRP’s. In this project, three different types of FRP’s were selected namely, UD CFRP, UD GFRP and BD CFRP. In order to meet the project’s aims, the experiment was carried out in two phases. First, specimens of similar dimensions were fabricated with and without the interleaving material. The second part of the project attempted to experimentally analyse the Mode I interlaminar fracture toughness of the carious specimens fabricated with the use of a UTM machine. The results were analysed using the compliance method and simple beam theory. Various correction factors were also further included in the simple beam theory to enhance the validity of the results obtained. It was found that Xantu.Layr was capable of improving the Mode I interlaminar fracture toughness of UD CFRP and UD GFRP. It, however, had a negative impact on the fracture toughness of BD CFRP. The fractured surfaces were also observed under an optical microscope to view the distribution of Xantu.Layr at the Interlaminar surface.